Vitamin D and adipose tissue—more than storage - Mutt, Shivaprakash J.; Hyppönen, Elina; Saarnio, Juha; Järvelin, Marjo-Riitta; Herzig, Karl-Heinz (Frontiers in Physiology, 2014)
The pandemic increase in obesity is inversely associated with vitamin D levels. While a higher BMI was causally related to lower 25-hydroxyvitamin D (25(OH)D), no evidence was obtained for a BMI lowering effect by higher 25(OH)D. Some of the physiological functions of 1,25(OH)2D3 (1,25-dihydroxycholecalciferol or calcitriol) via its receptor within the adipose tissue have been investigated such as its effect on energy balance, adipogenesis, adipokine and cytokine secretion. Adipose tissue inflammation has been recognized as the key component of metabolic disorders, e.g. in the metabolic syndrome. The adipose organ secretes more than 260 different proteins/peptides. However, the molecular basis of the interactions of 1,25(OH)2D3, vitamin D binding proteins (VDBPs) and nuclear vitamin D receptor (VDR) after sequestration in adipose tissue and their regulations are still unclear. 1,25(OH)2D3 and its inactive metabolites are known to inhibit the formation of adipocytes in mouse 3T3-L1 cell line. In humans, 1,25(OH)2D3 promotes preadipocyte differentiation under cell culture conditions. Further evidence of its important functions is given by VDR knock out (VDR -/-) and CYP27B1 knock out (CYP27B1 -/-) mouse models: Both VDR -/- and CYP27B1 -/- models are highly resistant to the diet induced weight gain, while the specific overexpression of human VDR in adipose tissue leads to increased adipose tissue mass. The analysis of microarray datasets from human adipocytes treated with macrophage-secreted products up-regulated VDR and CYP27B1 genes indicating the capacity of adipocytes to even produce active 1,25(OH)2D3. Experimental studies demonstrate that 1,25(OH)2D3 has an active role in adipose tissue by modulating inflammation, adipogenesis and adipocyte secretion. Yet, further in vivo studies are needed to address the effects and the effective dosages of vitamin D in human adipose tissue and its relevance in the associated diseases.